COMPLEMENTARY THERAPIES FOR PREMENSTRUAL SYNDROME: A COMPREHENSIVE REVIEW OF EVIDENCE-BASED INTERVENTIONS - Ayuk Naimah; Lailaturohmah; Eva Mesi Setiana (Kirana Publisher, 2025)
Premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD) are common conditions among adolescent girls, characterized by recurring physical, emotional, and behavioral symptoms that significantly affect quality of life and daily functioning. Conventional treatments, such as hormonal therapy and pharmacological agents, often have limitations in long‑term adherence and potential side effects, creating a need for holistic and non‑pharmacological alternatives. This review aims to analyze and synthesize evidence on complementary therapies that are effective in managing PMS and PMDD among adolescents. A comprehensive literature review was conducted using databases including PubMed, Scopus, ScienceDirect, ProQuest, and Google Scholar for studies published between 2018 and 2025. Search keywords included “premenstrual syndrome,” “adolescents,” “complementary therapy,” “cognitive behavioral therapy,” “mindfulness,” and “emotional freedom technique.” Inclusion criteria were randomized controlled trials (RCTs) and quasi-experimental studies evaluating non-pharmacological interventions with measurable outcomes related to PMS symptom reduction and psychological well-being. Ten studies met the criteria, highlighting the effectiveness of Cognitive Behavioral Therapy (CBT), Internet-based CBT (ICBT), Emotional Freedom Technique (EFT), mindfulness-based programs, and emotion-focused therapy. These interventions significantly reduced PMS and PMDD symptoms (p < 0.05), improved emotional regulation, resilience, and quality of life, and demonstrated effects that persisted up to 1–1.5 months post-intervention. Complementary therapies offer holistic, safe, and accessible strategies for managing PMS in adolescents, addressing both physical and emotional dimensions. Integrating these evidence-based approaches into adolescent health programs could provide sustainable benefits, reduce the burden of PMS while promoting psychological well-being and adaptive coping skills.